2018
DOI: 10.1016/j.bbrc.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

TGF beta inhibits expression of SP-A, SP-B, SP-C, but not SP-D in human alveolar type II cells

Abstract: TGF beta is a multifunctional cytokine that regulates alveolar epithelial cells as well as immune cells and fibroblasts. TGF beta inhibits surfactant protein A, B and C expression in fetal human lung and can inhibit type II cell proliferation induced by FGF7 (KGF). However, little is known about direct effects of TGF beta on adult human type II cells. We cultured alveolar type II cells under air/liquid interface conditions to maintain their state of differentiation with or without TGF beta. TGF beta markedly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Expression of SP-C was detectable as a ~ 7 kDa protein band in AT-II cells (4.92 ± 3.98 AU; n = 5) only and varied signi cantly in different cell types (p = 0.001). The sizes of the SP-C and SP-B proteins detected by western blotting were equivalent to sizes previously described [21]. The pattern of β-actin staining differed between non-reduced and reduced samples.…”
Section: Protein Expressionsupporting
confidence: 69%
“…Expression of SP-C was detectable as a ~ 7 kDa protein band in AT-II cells (4.92 ± 3.98 AU; n = 5) only and varied signi cantly in different cell types (p = 0.001). The sizes of the SP-C and SP-B proteins detected by western blotting were equivalent to sizes previously described [21]. The pattern of β-actin staining differed between non-reduced and reduced samples.…”
Section: Protein Expressionsupporting
confidence: 69%
“…Effects of active TGF-β1 on AE2 cells include the downregulation of SPs B and C, and other factors involved in surfactant biosynthesis [11,17]. During the expression of a porcine-derived active TGF-β1, the surface tension lowering capacity of broncho-alveolar lavage-derived surfactant has therefore been shown to be severely impaired.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that severe surfactant dysfunction and microatelectases represent the initial pathological findings during expression of active TGF-β1 and occur in the absence of any fibrotic remodeling in the early phase [11]. Surfactant dysfunction could be attributed to TGF-β1-induced downregulation of biophysically active surfactant proteins (SPs) B and C, and other components involved in surfactant biosynthesis in alveolar epithelial type II (AE2) cells [17], most likely due to lack of activity of thyroid transcription factor-1 in the nucleus [11]. In a second step, an increase in collagen fibrils in interalveolar septal walls was observed on day 14 of this model, whereas AE2 cells were subject to ultrastructural changes, characterized by a loss of surface area of the apical plasma membrane in relation to the baso-lateral plasma membrane [11].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, TGF-β1 markedly decreases the expression of fatty acid synthase 42 which we found downregulated in 3G8 cells (−1.95 fold change). This enzyme besides playing a pivotal role in lipid metabolism, is also implicated in the induction of angiogenesis 43 , in particular in cancer cells 44 .…”
Section: Discussionmentioning
confidence: 64%